2016
DOI: 10.2196/mental.5842
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Sites, Depression, and Anxiety: A Systematic Review

Abstract: BackgroundSocial networking sites (SNSs) have become a pervasive part of modern culture, which may also affect mental health.ObjectiveThe aim of this systematic review was to identify and summarize research examining depression and anxiety in the context of SNSs. It also aimed to identify studies that complement the assessment of mental illness with measures of well-being and examine moderators and mediators that add to the complexity of this environment.MethodsA multidatabase search was performed. Papers publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
428
1
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 535 publications
(462 citation statements)
references
References 146 publications
24
428
1
9
Order By: Relevance
“…The remaining three reviews included a mix of adults and adolescents in the sampling frame. Conclusions were consistent with those summarized for the adolescent populations above in that cross‐sectional research designs, retrospective reporting of symptoms and digital technology usage, and small and mixed patterns of associations were the norm and often limiting factors in drawing reliable conclusions in this area (Baker & Algorta, ; Seabrook et al, ). For example, in a 2016 review examining the association between frequency or time spent on SNS and depression, eight reported small positive associations, while twice as many found nonsignificant associations (Seabrook, Kern, & Rickard, ).…”
Section: What Do We Currently Know About the Association Between Adolsupporting
confidence: 79%
“…The remaining three reviews included a mix of adults and adolescents in the sampling frame. Conclusions were consistent with those summarized for the adolescent populations above in that cross‐sectional research designs, retrospective reporting of symptoms and digital technology usage, and small and mixed patterns of associations were the norm and often limiting factors in drawing reliable conclusions in this area (Baker & Algorta, ; Seabrook et al, ). For example, in a 2016 review examining the association between frequency or time spent on SNS and depression, eight reported small positive associations, while twice as many found nonsignificant associations (Seabrook, Kern, & Rickard, ).…”
Section: What Do We Currently Know About the Association Between Adolsupporting
confidence: 79%
“…Researchers have reported that the use of social networks such as Facebook, Twitter, or Instagram, and playing game on the Internet are associated with mental health problems of adolescents such as depression, psychological distress, and suicidal ideation (Mentzoni et al, ; Pantic et al, ; Sampasa‐Kanyinga & Lewis, ; L. Y. Lin et al, ). On the contrary, there are studies showing that social media use is related with less loneliness, higher self‐esteem, and life satisfaction (Pittman & Reich, ; Seabrook, Kern, & Rickard, ). Playing games on the Internet also increases cooperation and decreases aggressiveness (Gentile, ; Greitemeyer, Agthe, Turner, & Gschwendtner, ).…”
Section: Discussionmentioning
confidence: 99%
“…These individuals experiencing depressive symptoms may be prone to PSMU as they are to behavioral addictions such as gambling, Internet addiction, and eating disorders (Andreassen et al, 2016a; Ciccarelli et al, 2016; Korkeila, 2012; Lister et al, 2015; Rodgers et al, 2013). Another plausible scenario is that the association between PSMU and depressive symptoms is bidirectional—each influences and subsequently contributes to increases in the other (Seabrook et al, 2016). Future work involving more complex longitudinal designs would be helpful in this regard.…”
Section: Discussionmentioning
confidence: 99%